Usability, acceptability, and feasibility of a High-Density Microarray Patch (HD-MAP) applicator as a delivery method for vaccination in clinical settings. Issue 4 (30th November 2022) - Davies, Cristyn; Taba, Melody; Deng, Lucy; Karatas, Ceylan; Bag, Shopna; Ross, Charles; Forster, Angus; Booy, Robert; Skinner, S. Rachel
ABSTRACT: Background: High-density microarray patch (HD-MAP) vaccines may increase vaccine acceptance and use. We aimed to ascertain whether professional immunizers (PIs) and other healthcare workers (HCWs) in Australia, a High-Income Country (HIC), found the HD-MAP applicator usable and acceptable for vaccine delivery. Methods: This feasibility study recruited PIs and HCWs to administer/receive simulated HD-MAP administration, including via self-administration. We assessed usability against essential and desirable criteria. Participants completed a survey, rating their agreement to statements about HD-MAP administration. A subset also participated in an interview or focus group. Survey data were analyzed using descriptive statistics, and interviews were transcribed and subject to thematic analysis. Results: We recruited 61 participants: 23 PIs and 38 HCWs. Findings indicated high usability and acceptability of HD-MAP use across both groups by a healthcare professional or trained user and for self-administration with safety measures in place. Most administrations met essential criteria, but PIs, on average, applied the HD-MAP for slightly less time than the required 10-seconds, which the HCWs achieved. PIs perceived safety concerns about home administration but found layperson self-administration acceptable in an emergency, pandemic, and rural or remote settings. Conclusions: Participants found HD-MAP administration usable and acceptable. Usability and acceptability are likely to be improved through end-user education and training. Plain language summary: Professional immunizers and healthcare workers found high-density microarray patch devices highly usable and acceptable to administer vaccines. HD-MAPs may have advantages over intramuscular injections in clinical settings and in pandemics. Vaccination with HD-MAP may improve acceptance for those with needle-related anxiety.